Rush Revere and the brave pilgrims : time-travel adventures with exceptional Americans - Limbaugh, Rush H. (Threshold Editions, 2013)
Substitute middle-school history teacher Rush Revere takes his students back in time to experience American history as it happens aboard the Mayflower and on Plymouth Plantation.